Metabolic Flexibility and Mechanical Efficiency in Women Over-60 - Blasco-Lafarga, Cristina; Monferrer-Marín, Jordi; Roldán, Ainoa; Monteagudo, Pablo; Chulvi-Medrano, Ivan (Frontiers in Physiology, 2022)
Purpose: Ageing deteriorates Metabolic flexibility (MF). Moreover, recent studies show that glycolysis is barely increased despite impoverished lipid metabolism, in addition to increased relevance of muscle power in older adults. This study aims to analyze MF, i.e., fat and carbohydrates oxidation rates (FATox & CHOox), and the point of maximal fat oxidation (MFO) in a group of active women over-60. It also aims to delve into the role of power production and mechanical efficiency regarding MF. This will help to decipher metabolic behavior in response to increasing intensity. Methods: Twenty-nine women (66.13±5.62years) performed a submaximal graded cycling test, increasing 10W each 3-min15-s, from 30W to the second ventilatory threshold (VT2). Muscle power was adjusted with a Saris-H3 roller, together with a continuous gas analysis by indirect calorimetry (Cosmed K4b2). Pre and post-test blood lactate (BLa) samples were included. Frayn's equations, MFO & CHOoxpeak (mg/min/kg FFM) were considered for MF analysis (accounting for average VO2 and VCO2 in each last 60-s), whilst delta and gross efficiencies (DE% & GE%), and exercise economy (EC), were added for Mechanical Efficiency. Mean comparisons regarding intensities 60%, 80% and 100% at VT2, completed the study together with correlation analysis among the main variables. Results: MFO and CHOoxpeak were small (6.35±3.59 & 72.79±34.76 g/min/kgFFM respectively) for a reduced muscle power (78.21±15.84 W). Notwithstanding, GE% and EC increased significantly (p<0.01) with exercise intensity. Importantly, coefficients of variation were very large confirming heterogeneity. Whilst muscle power outcomes correlated significantly (p<0.01) with MFO (r=0.66) and age (r=-0.62), these latter failed to be associated. Only GE% correlated to CHOoxpeak (r=-0.61, p<0.01) regarding mechanical efficiency. Conclusions: Despite being active, women over-60 confirmed impaired substrates switching in response to exercise, from both FAT and CHO pathways. This limits their power production affecting exercise capacity. Our data suggest that decreased power with age has a key role above age per se in this metabolic inflexibility. Vice versa, increasing power seems to protect from mitochondrial dysfunction with ageing. New studies will confirm if this higher efficiency when coming close to VT2, where GE is the more informative variable, might be a protective compensatory mechanism.